2021
DOI: 10.5089/9781513573588.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fiscal Crises: A Machine Learning Approach

Abstract: In this paper I assess the ability of econometric and machine learning techniques to predict fiscal crises out of sample. I show that the econometric approaches used in many policy applications cannot outperform a simple heuristic rule of thumb. Machine learning techniques (elastic net, random forest, gradient boosted trees) deliver significant improvements in accuracy. Performance of machine learning techniques improves further, particularly for developing countries, when I expand the set of potential predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Specifically, the RF yields an average accuracy of 80%, while the logit model is 70%-75% accuracy accurate. In this regard, Hellwig (2021) found that RF approaches consistently outperform heuristic benchmarks and other statistical models. Other studies such as IMF (2021) found that the RF model performed better compared to other ML models in emerging markets and low-income countries, based on the sum of errors and the area under the curve (AUC).…”
Section: Random Forestmentioning
confidence: 91%
See 2 more Smart Citations
“…Specifically, the RF yields an average accuracy of 80%, while the logit model is 70%-75% accuracy accurate. In this regard, Hellwig (2021) found that RF approaches consistently outperform heuristic benchmarks and other statistical models. Other studies such as IMF (2021) found that the RF model performed better compared to other ML models in emerging markets and low-income countries, based on the sum of errors and the area under the curve (AUC).…”
Section: Random Forestmentioning
confidence: 91%
“…The leading indicator presented in this paper is based on the nonparametric approach proposed by Kaminsky, Lizondo, and Reinhart (1998) and incorporates calculations of the risk threshold level for each variable using the already proposed ALE technique. Contributions such as those made by Jarmulska (2020) or Hellwig (2021) demonstrate how ML models can be very good at forecasting fiscal stress. However, none of them takes these models to the construction of a leading indicator of macro-fiscal stress using risk thresholds.…”
Section: Leading Index Of Fiscal Stress For Machine Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Badia et al ( 2020) use machine learning models, specifically random forest algorithms, to predict fiscal crises and suggest, in line with Mullainathan and Spiess (2017), that these algorithms give better out-of-sample predictions by potentially incorporating a very large number of predictors without running into overfitting problems. Hence, as a model for making predictions, machine learning tools tend to outperform traditional approaches such as logit or probit (Hellwig (2021)). Machine learning tools do however have important downsides.…”
Section: Modelmentioning
confidence: 99%
“…The essence of these approaches is to select the most applicable hyperparameters for these machine learning methods. To choose the optimal hyperparameters, recent studies have tended to focus on the out‐of‐sample predictive performance and have used k‐fold cross‐validation to determine the hyperparameters according to the out‐of‐sample predictive accuracy (Chetverikov et al, 2016; Hellwig, 2021; Holopainen & Sarlin, 2017; Jarmulska, 2020). Although simple cross‐validation of the training and test groups can alleviate the overfitting problem to a certain extent, this type of hyperparameter selection still inevitably refers to the information of the test group.…”
Section: Introductionmentioning
confidence: 99%